Congestion Pricing, Slot Sales and Slot Trading in Aviation - Erik T. Verhoef (Tinbergen Institute, 2008)
This paper studies the regulation of an airline duopoly on a congested airport. Regulation should then address two market failures: uninternalized congestion, and overpricing due to market power. We find that first-best charges are differentiated over airlines if asymmetric, and completely drive out the least efficient airline from the market. This is not generally the case for an undifferentiated charge, which is found to be a weighted average of first-best charge rules for the two airlines, and is less-than-optimally efficient because of its inability to differentiate between them. Tradeable slots may yield the first-best outcome if the congestion externality is relatively important and the market power distortion relatively unimportant, but may be less efficient than non-intervention when the reverse is true.
Keywords: R41; R48; D62; 330; Airport congestion; congestion pricing; slot trading; tradeable permits; second-best; Bottleneck; Luftverkehr; Slotallokation; Flughafen; Duopol; Theorie